Subversive Activities of Hungarian and Polish Sabotage Groups in Carpathian Ukraine (1938–1939) - Vehesh, I.; Vehesh, M. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2022)
The article, based on archival and published documents, attempts to
highlight the international situation of the Czechoslovak Republic and
Transcarpathia on the eve of World War II. It proves that Hungary, throughout
the interwar period, pursued an aggressive irredentist policy aimed at
destabilizing Czechoslovakia and returning “its original territories”. This
revanchist activity culminated in 1938–1939, when the Hungarian government
sent diversion groups to Carpathian Ukraine, trying to destabilize the domestic
political situation in the region. A similar subversive operation was carried out
by Poland, which sought to establish a common Hungarian-Polish border by
completely eliminating Czechoslovakia. The authors argue that a “hybrid war”
was waged against young Carpathian Ukraine and in mid-March 1939 it
escalated into open intervention and occupation of the entire territory of the
region.
A. Voloshyn’s government together with the Czechoslovak troops made a
lot of efforts to protect the settlements of Carpathian Ukraine from the
destructive actions of enemy saboteurs. The formed divisions of the Carpathian
Sich and the Ukrainian gendarmerie were involved in the defense of the
borders.
Some parallels can be drawn with the events of 2014 in Ukraine, when
Russian troops annexed Crimea and occupied part of Donetsk and Luhansk
regions. In 1938–1939, the governments of Hungary and Poland assured the
world community that their troops did not exist in Transcarpathia. Similar is
the position of the leadership of the Russian Federation concerning the events
of 2014–2021 in Ukraine. У статті на основі архівних і опублікованих документів здійснюється спроба висвітлити міжнародне становище Чехословацької республіки й Закарпаття напередодні Другої світової війни. Доводиться, що
упродовж усього міжвоєнного періоду Угорщина проводила агресивну
іредентистську політику, спрямовану на дестабілізацію Чехословаччини,
на повернення «своїх споконвічних територій». Своєї кульмінації ця
реваншистська діяльність досягла в 1938–1939 роках, коли угорський
уряд направляв у Карпатську Україну диверсійні групи, які намагалися
дестабілізувати внутрішньополітичну ситуацію у краї. Аналогічну диверсійну роботу проводила Польща, яка прагнула встановити спільний
угорсько-польський кордон за рахунок повної ліквідації Чехословаччини.
Автори доводять, що проти молодої Карпатської України велася
«гібридна війна», яка в середині березня 1939 р. переросла у відкриту
інтервенцію та окупацію всієї території краю.